Modeling the effects of climate change on streamflow and stream temperature in the South Fork of the Stillaguamish River - Clarke, Katherine Mary (Western CEDAR, 2020)
The Stillaguamish River in northwest Washington State is an important regional water resource for local agriculture, industry, and First Nations tribes and a critical habitat for several threatened and endangered salmonid species, including the Chinook salmon. The river is currently subject to a temperature total maximum daily load, so it is important to understand how projected climate change will affect future stream temperatures and thus salmon populations. Snowpack is the main contributor to spring and summer streamflow and helps to mitigate stream temperatures as air temperatures rise through the summer in the South Fork of the Stillaguamish River. I used gridded historical meteorological data to calibrate the physically-based Distributed Hydrology Soil Vegetation Model and River Basin Model and then applied downscaled, gridded projected climate data to predict how a changing climate will influence hydrology and stream temperature in the South Fork basin through the end of the 21st century. My projected modeling results predict that increasing air temperatures will cause the South Fork basin to shift from a snow-dominated basin to a rain-dominated basin through the 21st century. This will result in up to a 60% increase in winter streamflow and a 50% decrease in basin-wide snowpack. Snowpack will begin to melt out earlier in the year, resulting in an average 58% decrease in spring and summer streamflow and increased stream temperatures. Average monthly stream temperatures could increase by as much as 6.4 ºC by the 2075 climate normal. The largest increases in stream temperatures occur in the spring due to a reduction in snowmelt. The warmest stream temperatures occur in July due to reduced streamflows and warmer air temperatures. Washington State Department of Ecology stream temperature thresholds for salmonid habitat are already being exceeding each year and will be increasingly exceeded through the end of the century. Projected increased stream temperatures will cause additional stress to already ...